Mental Strain and Chronic Stress among University Students with Symptoms of Irritable Bowel Syndrome - Marco D. Gulewitsch; Paul Enck; Juliane Schwille-Kiuntke; Katja Weimer; Angelika A. Schlarb (Gastroenterology Research and Practice)
Aim. To investigate the degree of mental strain and chronic stress in a German community sample of students with IBS-like symptoms. Methods and Materials. Following an internet-based survey about stress, this study recruited 176 German university students (23.45±2.48 years; 48.3% males) with IBS-like symptoms according to Rome III and 181 students without IBS (23.55±2.82 years; 50.3% males) and compared them regarding current mental strain (SCL-90-R) and the extend of chronic stress. Beyond this, IBS subtypes, IBS severity, and health care utilization were assessed. Results. Students fulfilling IBS criteria showed significantly elevated values of mental strain and chronic stress. Nearly 40% of the IBS group (versus 20% of the controls) reached a clinically relevant value on the SCL-90-R global severity scale. IBS subtypes did not differ in terms of mental distress or chronic stress. Somatization, anxiety, and the chronic stressors “work overload,” “social tension,” and “dissatisfaction with job” were most closely connected to IBS symptom severity. Regarding health care utilization, our results show that consulting a physician frequently was not associated significantly with elevated mental strain or chronic stress but with IBS symptom severity. Conclusion. Our data contribute additional evidence to the distinct association between psychological stress and IBS in community samples.